2020
DOI: 10.1371/journal.pntd.0008960
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk of dengue severity using demographic information and laboratory test results with machine learning

Abstract: Background Dengue virus causes a wide spectrum of disease, which ranges from subclinical disease to severe dengue shock syndrome. However, estimating the risk of severe outcomes using clinical presentation or laboratory test results for rapid patient triage remains a challenge. Here, we aimed to develop prognostic models for severe dengue using machine learning, according to demographic information and clinical laboratory data of patients with dengue. Methodology/Principal findings Out of 1,581 patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…In this study, we retrospectively included 65 patients from the 2015 Taiwan outbreak, but all patients were infected by the Cosmopolitan genotype strains of DENV-2 in a close cluster. In addition to potential bias arising due to a single predominant strain in the outbreak, elderly individuals constituted the major age group among the patients with severe dengue in the Taiwan outbreak, in contrast to the severe cases in children in southeastern Asia (Hoang et al, 2010) and South America (Allonso et al, 2014) as previously described (Tsai et al, 2016;Huang S. W. et al, 2020). Our dataset only came from the patients who seek medical advice in the hospital, which might exclude the mild cases who did not go to the hospital and resulted in the potential loss of true intrahost dynamics among mild cases.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we retrospectively included 65 patients from the 2015 Taiwan outbreak, but all patients were infected by the Cosmopolitan genotype strains of DENV-2 in a close cluster. In addition to potential bias arising due to a single predominant strain in the outbreak, elderly individuals constituted the major age group among the patients with severe dengue in the Taiwan outbreak, in contrast to the severe cases in children in southeastern Asia (Hoang et al, 2010) and South America (Allonso et al, 2014) as previously described (Tsai et al, 2016;Huang S. W. et al, 2020). Our dataset only came from the patients who seek medical advice in the hospital, which might exclude the mild cases who did not go to the hospital and resulted in the potential loss of true intrahost dynamics among mild cases.…”
Section: Discussionmentioning
confidence: 84%
“…Although it has been established that the circulating levels of NS1 antigen are positively correlated with DENV viremia [ 36 ] and are associated with severity [ 37 , 38 ], there is still debate about its usefulness as a biomarker [ 39 ]. In our study, no significant difference was found in the circulating levels of the NS1 antigen between the dengue patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue virus (DENV) occurs in over 100 countries causing nearly 100 million acute infections and half a million deaths each year [26,27]. The disease itself is characterized by an acute fever which is transmitted from mosquitos (Ae.…”
Section: Dengue Virusmentioning
confidence: 99%
“…Unfortunately, individuals infected with one serotype only produce antibodies capable of neutralizing that specific serotype, leaving the individual unprotected against the other 3 serotypes. Moreover, through antibody-dependent enhancement, re-infection by a different serotype increases the risk of severe dengue disease [26]. In 2019 a vaccine against DENV was approved for individuals aged 9-45 years and who had experienced a prior DENV infection.…”
Section: Dengue Virusmentioning
confidence: 99%